MEMPERTANYAKAN KEYAKINAN PADA KEMAMPUAN ARTIFICIAL INTELLIGENCE KHUSUSNYA STRONG AI: SEBUAH PERSPEKTIF REALIS KRITIS - Mukhlis, Meutia Irina (UI Scholars Hub, 2025)
Artificial intelligence (AI) is one of the most popular albeit divisive topics up for debate today. On the one hand, die-hard proponents of AI believe that AI may one day come close to possessing human-level intelligence or even supersedes it (this view of AI is called strong AI) while on the other, some seem unconvinced of the promises of strong AI and prefer to believe in a weaker form of AI, an AI that might be able to do some functions humans assign to them or simulate basic level of human intelligence. This paper leans more toward the latter’s view. Using critical realism and neo-Aristotelian virtue ethics as its theoretical framework and abduction as a method of reasoning and argumentation, this paper argues that belief in strong AI is misguided and caused by a flaw in the theoretical framework used to understand reality and the human condition, particularly in its ontological and ethical assumptions. On this view, the position of strong AI could not be upheld, since human intelligence is made up of different forms of intelligence including logical/rational, emotional and moral intelligence that could not all be neatly reduced and understood as a form of computation. Key words: Human Intelligence; Artificial Intelligence; Strong AI; Weak AI; Critical Realism; Neo-Aristotelian Virtue Ethics